(untitled) (Academicia Globe: Inderscience Research, 2023)
The article discusses the methodology of tax administration - an important aspect of any tax system, the continuous improvement of which is important to ensure effective collection, compliance and fairness of taxes. This article discusses the main problems faced by tax administration and suggests a strategy for improving them. To solve these problems, several strategies for improving tax administration are proposed. The improved methodology of tax administration helps to create a fair and efficient tax system that supports economic growth and sustainable development.